2017
DOI: 10.1007/s10711-017-0289-y
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Stein fillings with arbitrary fundamental group

Abstract: For any finitely presentable group G, we show the existence of an isolated complex surface singularity link which admits infinitely many exotic Stein fillings such that the fundamental group of each filling is isomorphic to G. We also provide an infinite family of closed exotic smooth four-manifolds with the fundamental group G such that each member of the family admits a non-holomorphic Lefschetz fibration over the two-sphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Many Lefschetz fibrations with explicit monodromies and non-complex total spaces have been constructed using the (twisted) fiber sum operation (see for instance [32], [30], [17], [22], [3] 2 , [2], [8]). They are non-holomorphic, however, do not have any (−1)-section since they are decomposable.…”
Section: Lefschetz Fibrations With Non-complex Total Spacementioning
confidence: 99%
“…Many Lefschetz fibrations with explicit monodromies and non-complex total spaces have been constructed using the (twisted) fiber sum operation (see for instance [32], [30], [17], [22], [3] 2 , [2], [8]). They are non-holomorphic, however, do not have any (−1)-section since they are decomposable.…”
Section: Lefschetz Fibrations With Non-complex Total Spacementioning
confidence: 99%
“…• If (Y, y) is Cohen-Macaulay and if the hyperplane section (f −1 (0), y) has an isolated singularity, property (1) implies that (f −1 (0), y) is also Cohen-Macaulay. Property (2) implies then that it is normal.…”
Section: Sweeping Out the Cone With Hyperplane Sectionsmentioning
confidence: 99%
“…Ohta and Ono [34] showed that there exist Milnor fillable contact 3-manifolds which admit an infinite number of minimal strong symplectic fillings, pairwise not homotopy equivalent. Later, Akhmedov and Ozbagci [1] proved that there exist Milnor fillable contact 3-manifolds which admit even an infinite number of Stein fillings pairwise non-diffeomorphic, but homeomorphic. Moreover, by varying the contact 3-manifold, the fundamental groups of such fillings exhaust all finitely presented groups.…”
Section: Introductionmentioning
confidence: 99%
“…The later problem has been studied for the standard family of hyperelliptic Lefschetz fibrations (with total spaces CP 2 #(4g + 5)CP 2 ) in [27,31,39], using the computations in the mapping class group, and such results are useful in constructing (exotic) Stein fillings [1,3].…”
Section: Introductionmentioning
confidence: 99%